2017
DOI: 10.1111/psyp.12885
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological characterization of facilitation and interference in the picture‐word interference paradigm

Abstract: The picture-word interference paradigm is often used to investigate the processes underlying word production. In this paradigm, participants name pictures while ignoring distractor words. The aim of this study is to investigate the processes underlying this task and how/when they differ from those involved in simple picture naming. It examines the electrophysiological signature of general interference (longer response times with than without distractors) and facilitation (shorter response times for distractor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…Taken together, our results suggest that semantic distractors affect the processing of the target pictures in more than one way and that both accounts of semantic interference, i.e., lexical competition and response exclusion, seem to capture a part, but not all aspects of the semantic interference effect. This conclusion is in accordance with findings using fMRI (de Zubicaray et al, 2012a,b) and also with the finding that superimposed distractors affect picture naming at various points during response preparation (Bürki, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together, our results suggest that semantic distractors affect the processing of the target pictures in more than one way and that both accounts of semantic interference, i.e., lexical competition and response exclusion, seem to capture a part, but not all aspects of the semantic interference effect. This conclusion is in accordance with findings using fMRI (de Zubicaray et al, 2012a,b) and also with the finding that superimposed distractors affect picture naming at various points during response preparation (Bürki, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Since the two approaches lead to very similar estimates for our study, we will focus here on the informed rescaling method. A picture naming study by Bürki (2017), which compared ERPs to pictures with unrelated written distractor words to those without distractors, provides some information for informed rescaling, at least for the first 250 ms post stimulus onset, that is until the stimuli disappeared in our experiment. Bürki (2017) found differences in ERP amplitudes emerged from about 200 ms post stimulus presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Zhu et al (2015) observed an ERP correlate of phonological facilitation between 450 -600 ms, that is, in a later time window than the one in which they observed a correlate of sematic interference. Other studies (Blackford et al, 2012;Bürki, 2017) did not find any ERP correlate of phonological facilitation at all.…”
Section: Erp Correlates Of Semantic Interference and Phonological Facilitation In Pwimentioning
confidence: 70%
“…The use of paradigms such as picture naming and picture-interference naming, in combination with EEG/MEG ( Roelofs et al, 2016 ; Bürki, 2017 ) and fMRI ( De Zubicaray et al, 2002 ) methods, have contributed to the understanding of the time course of word production and hence could provide valuable information about the neural markers of L1 attrition at the phonological and phonetic encoding stages. The logic is similar to the one described above for the evaluation of lexico-semantic L1 attrition.…”
Section: Building a Framework: In Search Of The Neural Correlates Of Attritionmentioning
confidence: 99%